'Ju, ich jag': A Three-part Song in the Mönch von Salzburg Corpus in Translingual Perspective. (2nd January 2020) - Murray, David
Abstract : Among the important corpus of late fourteenth-century songs transmitted under the cipher of the anonymous 'Monk of Salzburg', one piece stands out. In a primarily monophonic body of songs, 'Ju, ich jag' is both the only three-part canon and the only secular piece for which a specific model can be found. Composed to the melody of the Old French 'chace' or hunt-song 'Umblemens vos pri merchi', 'Ju, ich jag' records the meetings between Romance and Germanic understandings of the pastoral genre at the archiepiscopal court of Salzburg. Further, the Marian Leich 'O pia Maria', a Latin 'contrafactum' of 'Ju, ich jag', edited here for the first time, bears witness to the porousness between devotional and worldly song in the later Middle Ages. Viewing this group of songs through the perspective of translingualism, this article argues that the movement of cultural artefacts from one linguistic area to another is as much influenced by literary discourses and the connotation of poetic forms as it is by language, and locates it in the culturally complex milieu of the ecclesiastical court.